2019
DOI: 10.1302/0301-620x.101b1.bjj-2018-0869.r1
|View full text |Cite
|
Sign up to set email alerts
|

The outcome following spinal instrumentation in haemodialyzed patients with pyogenic spondylodiscitis

Abstract: Aims The aim of this study was to evaluate the outcome of spinal instrumentation in haemodialyzed patients with native pyogenic spondylodiscitis. Spinal instrumentation in these patients can be dangerous due to rates of complications and mortality, and biofilm formation on the instrumentation. Patients and Methods A total of 134 haemodialyzed patients aged more than 50 years who underwent surgical treatment for pyogenic spondylodiscitis were included in the study. Their mean age was 66.4 years (50 to 83); 66 w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
35
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 12 publications
(39 citation statements)
references
References 34 publications
2
35
2
Order By: Relevance
“…According to the classification of Pola et al ., 94.1% of the cohort (80/85 patients) had structural instability (type B) or neurological compromise (type C), which theoretically requires surgical treatment 18 . Compared with the results of previous reports 15,42 , our results showed that PVO patients with cirrhosis are considered to have an even more extensive spinal involvement than other groups of PVO patients. We hypothesized that immune dysfunction 11 and impaired bony microarchitecture 14 contributes to aggressive infection.…”
Section: Discussioncontrasting
confidence: 67%
See 4 more Smart Citations
“…According to the classification of Pola et al ., 94.1% of the cohort (80/85 patients) had structural instability (type B) or neurological compromise (type C), which theoretically requires surgical treatment 18 . Compared with the results of previous reports 15,42 , our results showed that PVO patients with cirrhosis are considered to have an even more extensive spinal involvement than other groups of PVO patients. We hypothesized that immune dysfunction 11 and impaired bony microarchitecture 14 contributes to aggressive infection.…”
Section: Discussioncontrasting
confidence: 67%
“…Previous studies reported the early mortality of PVO patients, including in-hospital mortality or 90-day mortality ranging from 2.8% to 16.8% 2732 . A recent study investigating the clinical outcome of PVO patients with hemodialysis reported an in-hospital mortality of 14.9% and 1-year mortality of 22.4% 15 . Compared with the results of previous studies, the mortality in our PVO patients with cirrhosis was considerably higher.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations